(untitled) (Research, Society and Development, 2022)
The study aimed to identify possible psychological impacts and on the learning process of elementary school I students during the COVID-19 pandemic, as well as the categorization and discussion of such impacts. In addition, the identification of protective factors that can contribute to mitigate the impacts and risk that may contribute to potentiate. This is a bibliographical, exploratory and qualitative research, since it sought to deepen the psychological impacts and the learning process during the pandemic, as well as the knowledge, analysis and survey of existing theoretical contributions on the subject. The study used recent research on the consequences of social isolation and the suspension of classroom classes for children, which is the population most affected due to their vulnerability. Furthermore, materials about the importance of the interaction of the child with a group of peers so that there is learning, according to Vygotsky’s socio-interactionist theory. It is perceived, then, that it is necessary to create an environment with the predominance of protective factors, in order to prevent possible psychological impacts and in the learning process.